Ett kulturminne i vardande - Grahn, Wera (Tidsskrift for kulturforskning, 2009)
Why do people who hardly ever attend church suddenly become the forefront defenders of the church building when it is threatened to be demolished? What does the church mean to these people that paradoxically enough seems to care about the building though they previously never seem to have paid it particular attention? Which values do they assign to the church if its significance is not based on Christian values? To get an answer to these questions, an investigation has been made in the small village of Ålgård, in the south-west of Norway. The congregation wished to demolish their church to make room for a new one, but a main part of the non-active members of the church wanted to keep it.